FZD6 triggers Wnt–signalling driven by WNT10BIVS1 expression and highlights new targets in T‐cell acute lymphoblastic leukemia. Issue 3 (16th February 2021) - Cassaro, Adriana; Grillo, Giovanni; Notaro, Marco; Gliozzo, Jessica; Esposito, Ilaria; Reda, Gianluigi; Trojani, Alessandra; Valentini, Giorgio; Di Camillo, Barbara; Cairoli, Roberto; Beghini, Alessandro
Abstract: Wnt/Fzd signaling has been implicated in hematopoietic stem cell maintenance and in acute leukemia establishment. In our previous work, we described a recurrent rearrangement involving the WNT10B locus (WNT10B R ), characterized by the expression of WNT10B IVS1 transcript variant, in acute myeloid leukemia. To determine the occurrence of WNT10B R in T‐cell acute lymphoblastic leukemia (T‐ALL), we retrospectively analyzed an Italian cohort of patients ( n = 20) and detected a high incidence (13/20) of WNT10B IVS1 expression. To address genes involved in WNT10B molecular response, we have designed a Wnt‐targeted RNA sequencing panel. Identifying Wnt agonists and antagonists, it results that the expression of FZD6, LRP5, and PROM1 genes stands out in WNT10B IVS1 positive patients compared to negative ones. Using MOLT4 and MUTZ‐2 as leukemic cell models, which are characterized by the expression of WNT10B IVS1, we have observed that WNT10B drives major Wnt activation to the FZD6 receptor complex through receipt of ligand. Additionally, short hairpin RNAs (shRNAs)‐mediated gene silencing and small molecule‐mediated inhibition of WNTs secretion have been observed to interfere with the WNT10B/FZD6 interaction. We have therefore identified that WNT10B IVS1 knockdown, or pharmacological interference by the LGK974 porcupine (PORCN) inhibitor, reduces WNT10B/FZD6 protein complex formation and significantly impairs intracellular effectors and leukemic expansion. These results describe the molecular circuit induced by WNT10B and suggest WNT10B/FZD6 as a new target in the T‐ALL treatment strategy.